Increasing Physical Activity and Exercise in Lung Cancer: Reviewing Safety, Benefits, and Application. Issue 6 (June 2015) - Bade, Brett C.; Thomas, D. David; Scott, JoAnn B.; Silvestri, Gerard A.
Abstract : Lung cancer continues to be a difficult disease frequently diagnosed in late stages with a high mortality and symptom burden. In part because of frequent lung comorbidity, even lung cancer survivors often remain symptomatic and functionally limited. Though targeted therapy continues to increase treatment options for advanced-stage disease, symptom burden remains high with few therapeutic options. In the last several decades, exercise and physical activity have arisen as therapeutic options for obstructive lung disease and lung cancer. To date, exercise has been shown to reduce symptoms, increase exercise tolerance, improve quality of life, and potentially reduce length of stay and postoperative complications. Multiple small trials have been performed in perioperative non–small-cell lung cancer patients, although fewer studies are available for patients with advanced-stage disease. Despite the increased interest in this subject over the last few years, a validated exercise regimen has not been established for perioperative or advanced-stage disease. Clinicians underutilize exercise and pulmonary rehabilitation as a therapy, in part because of the lack of evidence-based consensus as to how and when to implement increasing physical activity. This review summarizes the existing evidence on exercise in lung cancer patients.